2019
DOI: 10.1007/s10854-019-00946-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions, energy storage performances and electrocaloric effect of the lead-free Ba0.85Ca0.15Zr0.10Ti0.90O3 ceramic relaxor

Abstract: Lead-free Ba0.85Ca0.15Zr0.10Ti0.90O3 (BCZT) ceramic exhibits excellent dielectric, ferroelectric and piezoelectric properties at the Morphotropic Phase Boundary (MPB). Previously, we demonstrated that the use of the anionic surfactant Sodium Dodecyl Sulfate (SDS, NaC12H25SO4) could enhance the dielectric properties of BCZT ceramic using surfactant-assisted solvothermal processing [1]. In the present study, structural, dielectric, ferroelectric properties, as well as electrocaloric effect and energy storage per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 51 publications
(59 reference statements)
4
34
0
Order By: Relevance
“…To confirm such inference, Raman spectra are measured before and after magnetizing the samples under magnetic field of 2 T. The inset in Figure a shows the results for BCZTF 0.04 at 85 K, where the samples possess the MPB structure. The peak at around 297 cm −1 , which is the typical mode of the tetragonal ferroelectric phase, becomes more obvious after magnetization, indicating the structure change of the MPB phase. For the samples with x = 0.40, MD effect is not observed in the measured temperature range 10–310 K as its MPB ferroelectric phase is suppressed by quantum fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm such inference, Raman spectra are measured before and after magnetizing the samples under magnetic field of 2 T. The inset in Figure a shows the results for BCZTF 0.04 at 85 K, where the samples possess the MPB structure. The peak at around 297 cm −1 , which is the typical mode of the tetragonal ferroelectric phase, becomes more obvious after magnetization, indicating the structure change of the MPB phase. For the samples with x = 0.40, MD effect is not observed in the measured temperature range 10–310 K as its MPB ferroelectric phase is suppressed by quantum fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…5(a) depicts P-E hysteresis loops registered at different temperatures at the driving frequency of 1 Hz, as in our recent paper Ref. [25]. The same frequency (1 Hz) was kept to avoid any influence of the frequency as reported by Cheng et al [53].…”
Section: Electrocaloric Effect In Rod-like Bczt Ceramicsmentioning
confidence: 95%
“…However, BaTiO 3 exhibits low dielectric properties compared to lead-based materials and its dielectric constant below the Curie temperature (T c = 393 K) rapidly drops due to the tetragonal/cubic phase transition [20,21]. To overcome the drawback, the Ba 1-x Ca x Zr y Ti 1-y O 3 system is engineered by introducing Ca 2+ and Zr 4+ into the crystal lattice of BaTiO 3 , to replace Ba 2+ and Ti 4+ , respectively, with improved dielectric properties due to enhanced relaxor behavior of Ba 1-x Ca x Zr y Ti 1-y O 3 ceramics [22][23][24][25][26]. Moreover, as reported by Liu and Ren [27], Ba 0.85 Ca 0.15 Zr 0.10 Ti 0.90 O 3 (BCZT) phase exhibits interesting dielectric, ferroelectric, and piezoelectric properties at the morphotropic phase boundary (MPB), which is comparable to those of PZT ceramics [15].…”
Section: Introduction mentioning
confidence: 99%
“…This lead-free ceramic possesses a broad frequency-dependent peak corresponding to the temperature-dependent dielectric susceptibility, lower remnant polarization, and slimmer hysteresis loops due to the relaxor ferroelectric nanodomains, which are essential for realizing extremely high energy densities and efficiencies. [14][15][16][17] Moreover, it was reported that BCZT ceramics possess low dielectric loss (tan d) (1-3%), which is encouraging for obtaining high-efficiency energy storage density. 10,[18][19][20][21] BCZT relaxor ferroelectric ceramics have been attracting much attention for energy storage applications and electrocaloric cooling devices owing to their outstanding dielectric and ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%